The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0103-51502010000400016
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do tratamento fisioterapêutico na pré-eclampsia

Abstract: ResumoIntrodução: As síndromes hipertensivas gestacionais (SHG) caracterizam uma gestação de alto risco, ocorrendo em 10% a 22% das gestantes, e estando a ela relacionadas as intercorrências clínicas maternofetais. Objetivos: Este trabalho teve por objetivo geral realizar uma pesquisa bibliográfi ca sobre o efeito do tratamento fi sioterapêutico na pré-eclampsia e, em específi co, avaliar os efeitos do tratamento fi sioterapêutico na diminuição da pressão arterial em gestantes que apresentam fatores de risco p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Recently, recommendations about exercise in pregnant women with hypertension or at risk of PE development have been studied with the objective of trying to reduce the deleterious effects of hypertensive disorders in pregnancy, including the reduction of the incidence of PE [1821]. The mechanism involved would be that PE could be prevented through physical exercise by reducing blood pressure levels and promoting better cardiovascular fitness in pregnant women [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, recommendations about exercise in pregnant women with hypertension or at risk of PE development have been studied with the objective of trying to reduce the deleterious effects of hypertensive disorders in pregnancy, including the reduction of the incidence of PE [1821]. The mechanism involved would be that PE could be prevented through physical exercise by reducing blood pressure levels and promoting better cardiovascular fitness in pregnant women [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Souza et al [52], the authors emphasize the idea that the physiotherapist is responsible for guiding changes in the pregnant woman's life habits in order to reduce risks. Researchers in 2016 identified that pregnant women who participated in any physical activity at the beginning of the first trimester of pregnancy achieved a reduction of up to 35% on the risk of acquiring hypertensive disease, or even with a favorable prognosis and greater benefits when practiced in the year prior to pregnancy [53].…”
Section: Obstetric Therapies With Oral Antidiabetic Metformin Hydrochmentioning
confidence: 99%